Dampak Gaya Kepemimpinan Terhadap Motivasi Kerja Aparat Desa Lokotoy Kecamatan Banggai Utara Kabupaten Banggai Laut: The Impact of Leadership Style on Work Motivation of Lokotoy Village Officials, North Banggai District, Banggai Laut Regency - Andrie Firmansyah (Fakultas Ekonomi, Universitas Tompotika Luwuk, 2025)
The research question is whether Leadership Style significantly influences the Work Motivation of Lokotoy Village Officials, North Banggai District, Banggai Laut Regency. The data analysis technique used in this study was simple linear regression analysis. The results of the data processing obtained a simple linear regression equation of Y = 16.460 + 0.415X. The correlation coefficient value was 0.257. This value indicates that the relationship between the independent variable, Leadership Style, used in this study, has a weak relationship with the dependent variable, Work Motivation, at 25.7% (0.2571 x 100%), because it has an interval of 0.20–0.399, categorized as Weak. The coefficient of determination obtained in this study, 0.066, indicates that the independent variable, Leadership Style (X), contributes 6.6% to the dependent variable, Work Motivation (Y), with the remaining 93.4% influenced by other factors not examined. The calculated t-value is 0.881 ˃ t-table 1.795 with a probability value of 0.397. This indicates that the independent variable, Leadership Style (X), does not have a significant effect on the dependent variable, Work Motivation (Y).